Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
3(6 - x) + 2x = 15
18 - 3
-3x+2x = 15
18 - x = 15
-x = 15 - 18
-x =- 3
x = 3
easy - peasy
Answer:
x=3
Step-by-step explanation:
PEMDAS
Or parenthesis, exponent, multiply, divide, addition, and subtraction. (Order of operations)
3(6-x) + 2x = 15
Start with multiplying
18 - 3x + 2x = 15
then combine like terms
18 - x = 15
subtract 18 from each side
-x = -3
times each side by -1 to remove the negative
x = 3
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.